(untitled) (Research, Society and Development, 2023)
The objective was to report the registration and dissemination of an Educational Technology in competent bodies and instances, as well as, on social platforms, through registration with ANCINE and REA/PEA UFPR, dissemination on social networks such as Instagram, Facebook, Youtube, WhatsApp, and TikTok, and building a poster. The video was recorded on the REA/PEA UFPR platform, and on ANCINE, as a non-advertising work. It was also released on Youtube, Instagram, Facebook of the NEPES UFPR group and on other social networks such as WhatsApp, and TikTok (@mucosite_saude). The poster, with the title of the video, its objective and the QRcode, was placed in the corridors of the UFPR faculty and at the Hospital das Clínicas, more specifically in the STMO rooms. Social media represent an easy, dynamic and attractive way of disseminating knowledge, especially among children and adolescents, who are in recurring contact with social platforms. The application of this production will enable the development of other studies and new proposals for technologies applicable in pediatric oncology and HSCT; as well as, it will encourage the dissemination of technologies produced in the field of nursing and health.